Análisis Multitemporal De Cambios De Cobertura De La Tierra En El Páramo De Almorzadero En El Departamento De Norte De Santander Colombia Entre Los Años 1992, 2014 Y 2023 (2025)
The Almorzadero moorland is located in the northeast of Colombia, between the departments of Santander and Norte de Santander. For this analysis, the northern area of the moorland was taken into account, which is located in the department of Norte de Santander. Taking into account the pressure that the moors exert on a daily basis due to the agricultural frontier, other anthropogenic pressures and climate change, a multi-temporal analysis was carried out between the years 1992, 2014 and 2023, using the program as a tool for the study. Arcgis PRO, which allowed the management of information from LandSat images of different generations, to carry out supervised classifications, the application of the NDVI Vegetation Index, and the achievement of the components main ones, and also obtain the coverage change maps for the two temporalities